Cell Sorting-Assisted Microarray Profiling of Host Cell Response to Cryptosporidium parvum Infection - Yang, Yi-Lin (American Society for Microbiology (ASM), 2010)
To study the transcriptional response of mammalian cells to infection with the intracellular apicomplexan parasite Cryptosporidium parvum, infected and uninfected cells were recovered from C. parvum-infected cell monolayers. This approach, which contrasts with a more conventional experimental design that compares infected to uninfected cell monolayers, enabled the identification of functional categories of genes that are differentially transcribed as a direct consequence of the presence of intracellular parasites. Among several categories of upregulated genes, glycoprotein metabolism was significantly overrepresented. To investigate whether these transcriptional changes affected the composition of the surface of infected cells, cells were probed with fluorescently labeled lectins. Among a panel of seven lectins, soybean agglutinin, which recognizes N-acetyl-d-galactosamine, generated the largest difference in fluorescence between infected and uninfected cells. The origin of the fluorescent signal emitted by infected cells was further investigated and attributed to the overexpression of glycoprotein on the surface of infected cells, as well as the presence of glycoprotein located in the proximity of intracellular parasites.